The Inhibitory Effects of 6-Thioguanine and 6-Mercaptopurine on the USP2a Target Fatty Acid Synthase in Human Submaxillary Carcinoma Cells - Cheng, Chiao-Pei; Liu, Shu-Ting; Chiu, Yi-Lin; Huang, Shih-Ming; Ho, Ching-Liang (Frontiers in Oncology, 2021)
Overexpression of the deubiquitinase USP2a leads to stabilization of fatty acid synthase (FAS), the levels of which are often elevated in aggressive human cancers. Consequently, there is an urgent need for inhibitors to suppress the deubiquitination activity of USP2a so as to upregulate FAS protein degradation. We first analyzed the relationship between the expression level of USP2a and survival using The Cancer Genome Atlas Head-Neck Squamous Cell Carcinoma (HNSC) data collection. Our results suggested survival rates were lower among HNSC patients expressing higher levels of USP2a. We then investigated two thiopurine drugs, 6-thioguanine (6-TG) and 6-mercaptopurine (6-MP), to determine whether they could potentially serve as inhibitors of USP2a. Western blot analysis showed that levels of two USP2a target proteins, FAS and Mdm2, were dose-dependently decreased in A253 submaxillary carcinoma cells treated with 6-TG or 6 MP. Responding to the degradation of Mdm2, levels of p53 were increased. We found that 6-TG and 6-MP also suppressed levels of both USP2a mRNA and protein, suggesting these two thiopurines do not act solely through direct inhibition of USP2a. The effects of 6-TG and 6-MP were not cell type-specific, as they elicited similar decreases in FAS protein in leukemia, prostate and cervical cancer cell lines. 6-TG and 6-MP had effects on several cell cycle proteins, including another USP2a target protein, cyclin D1. The populations of cells in subG1 and S phase were increased by 6-TG and 6-MP, which was accompanied by reductions in G1 phase cells. In untreated cells, USP2a transfection increased FAS and cyclin D1 levels compared to an enzyme-dead USP2a C276A mutant, which lacked deubiquitinating activity. However, USP2a transfection failed to reverse the suppressive effects of 6 TG and 6-MP on FAS levels. In summary, these findings suggest 6-TG and 6-MP reduce the stability of some USP2a targets, including FAS and Mdm2, by inhibiting USP2a-catalyzed deubiquitination in some cancer cells. Our work also provides repurposing evidence supporting 6 TG and 6-MP as target therapeutic drugs, such as USP2a/FAS in this study.